Pengembangan Media Komjinasi (Komik Imajinasi) pada Pembelajaran Bahasa Indonesia untuk Siswa Kelas V Sekolah Dasar - Romadon; Rachma Putri Dinanti Dinanti; Feri Ardiansah (Universitas Muhammadiyah Bangka Belitung, 2020)
The purpose of this research is to develop learning media Komjinasi (Comic Imagination) in Indonesian Language Learning for Class V Students of SD Negeri 18 Simpang Teritip. This type of research is Research and Development. Using the Borg and Gall model that the researcher has modified into eight stages including potential problems, data collection, product design, expert validation, product revision, small-scale trials, large-scale trials, and the final product. The research instrument used interviews, observations, and questionnaires. Large-scale trials were carried out by 16 (sixteen) students which later became the final result of media products as learning media. The results of research from material experts 1 and 2 obtained an average score of 91% in the very good category. The results of the validation of 1 (one) and 2 (two) media experts obtained an average score of 98% very well. Small-scale trials from the material aspect obtained an average score of 88%, small-scale trials from the media aspect obtained an average score of 74%, while small-scale trials from the benefit aspect obtained an average score of 88% and the three aspects were categorized as very good. For large-scale trials from the material aspect obtained an average score of 88%, the large-scale trials from the media aspect obtained an average score of 83%, while large-scale trials from the aspects of benefits obtained an average score of 74%, and the three aspects categorized as very good. The three results of the expert team's validation assessment and testing showed that the imaginary comics (Imagination Comics) were in the “Good” category and were appropriate as learning media.